KINERJA KEUANGAN, CORPORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE DAN NILAI PERUSAHAAN - Sari, Damayanti Astika; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out empiricalevidencesabout: (a) the influence of financial performance ROE to the firm value; (b) the influence of CSR disclosure to the correlation between ROE and the firm value; (c) the influence of managerial ownership to the correlation between ROE and the firm value. The samplesare manufacturing companies in the basic industry and chemical sector which are listed in Indonesia Stock Exchange during 2009-2013 periods. 23 companies and 115 observation have been selected as samples. The data analysis has been done by using simple linear regressions analysis forhypothesis 1 and the multiple linear regressions analysis which has been done by using Moderated Regressions Analysis (MRA) for the hypothesis 2 and 3. The results of the research are: (a) shows that ROE has positive influence onthe firm value. It shows that the Return on Equity (ROE) has beenresponded positive by the investors; (b) the CSR disclosurepositively moderates the influence of financial performance on the firm value. It means that when the CSR activity is disclosed widespread by the company, the respons of the investors to the financial performance is getting high; (c) managerial ownership positively moderates the influence of ROE on the firm value. it shows that when the managerial ownership is getting high, the respond of the investors on the financial performance is getting high as well.Keywords : Financial Performance, Firm Value, CSR Disclosure, Managerial Ownership.